Burkholderia gladioli CGB10: A Novel Strain Biocontrolling the Sugarcane Smut Disease - Cui, Guobing; Yin, Kai; Lin, Nuoqiao; Liang, Meiling; Huang, Chengwei; Chang, Changqing; Xi, Pinggen; Deng, Yi (Microorganisms (Basel), 2020)
In this study, we isolated an endophytic Burkholderia gladioli strain, named CGB10, from sugarcane leaves. B. gladioli CGB10 displayed strong inhibitory activity against filamentous growth of fungal pathogens, one of which is Sporisorium scitamineum that causes sugarcane smut, a major disease affecting the quality and production of sugarcane in tropical and subtropical regions. CGB10 could effectively suppress sugarcane smut under field conditions, without itself causing any obvious damage or disease, thus underscoring a great potential as a biocontrol agent (BCA) for the management of sugarcane smut. A toxoflavin biosynthesis and transport gene cluster potentially responsible for such antifungal activity was identified in the CGB10 genome. Additionally, a quorum-sensing gene cluster was identified too and compared with two close Burkholderia species, thus supporting an overall connection to the regulation of toxoflavin synthesis therein. Overall, this work describes the in vitro and field Sporisorium scitamineum biocontrol by a new B. gladioli strain, and reports genes and molecular mechanisms potentially involved.